Child maltreatment and memory.[article]. - Goodman, Gail S.
Exposure to childhood trauma, especially child maltreatment, has important implications for memory of emotionally distressing experiences. these implications stem from cognitive, socio-emotional, mental health, and neurobiological sequences of maltreatment and can be at least partially explained by current theories concerning the effects of childhood trauma. In this review, two main hypotheses are advanced:(a) Maltreatment in childhood is associated with especially robust memory for emotionally distressing material in many individuals ,but(b)maltreatment can impair memory for such material in individuals who defensively avoid it. Support for these hypotheses comes from research on child abuse victims' memory and suggestibility regarding distressing but non abusive events, memory for child abuse itself, and autobiographical memory. However, more direct investigations are needed to test precisely when and how childhood trauma affects memory for emotionally significant, distressing experiences. Legal implications and future directions are discussed.